How Does User’s Learning Style Impact the Effectiveness of Online Customer Service? - Agourram, Hafid; Agourram, Hasna (European Scientific Journal, ESJ, 2018)
National culture determines the shared learning style of its people. In a particular culture, people may learn best when content is made of videos, graphs, pictures, charts. In another culture they learn better by talking, discussing and chatting. In another culture, by reading and writing, and in other cultures by experimenting and practicing. At the same time, transactional web sites assume a static customer learning style. The design of the site usually reflects the designer’s learning style and cognitive style which in turn reflects the learning style type of people in particular culture. However, the sharp increase number of transactional web sites draw the attention and the focus of management to the quality and the effectiveness of customer service web pages. We argue that the fit between the design of the content of customer service pages with the customer’s learning style may increase online customer service effectiveness.